Role of central bank independence on monetary integration and business cycle synchronization in the economic community of West African States - Louis-Joel Basneouinde Diendere; Achille Augustin Diendere; Jude Eggoh (Cogent Economics & Finance, 2024)
This article examines the effects of monetary integration on the synchronization of the business cycle within ECOWAS (Economic Community of West African States) and contributes to the economic literature dealing with these aspects. First, the indicators of de facto and de jure central bank independence are considered to examine the role of central bank independence in the relationship between monetary integration and business cycle synchronization. Second, the ARDL error correction estimator is used to analyze both short- and long-run relationships and to address potential problems related to endogenous variables. Using panel data covering 105 country pairs from 1990 to 2020, the estimation results show a positive and statistically significant effect of monetary integration on the long-run synchronization of the business cycle. Regarding short-term synchronization, the conclusions are mixed. Overall, this study argues for the implementation of economic policy measures aimed, among other things, at complying with convergence criteria, strengthening trade agreements, and ensuring the independence of the central bank of the future monetary union. This article demonstrates that monetary integration promotes long-term business cycle synchronization within ECOWAS, highlighting the importance of central bank independence. Using panel data and an ARDL method, it reveals significant effects of this integration while noting mixed results in the short term. The findings advocate for economic policies focused on convergence criteria, strengthened trade agreements, and central bank independence to enhance regional stability.
Keywords: F36; E31; E58; E32; O55; 330; inflation; ECOWAS; business cycle synchronization; central bank independence; Monetary integration; panel ARDL process